Efficacy Evaluation Study for Microburst Insulin Infusion: A Novel Model of Care - Howard, Steven W.; Zhang, Zidong; Linomaz, Jacob; Lam, Wing; Qian, Zhengmin; Thurman, Jerry; BeLue, Rhonda (Frontiers in Public Health, 2021)
Objectives: This study aims to evaluate the impact of Microburst Insulin Infusion (MII) treatment on Type 1 and 2 diabetic patients' HbA1c, lipids, peripheral neuropathy, and patient-reported health status. Methods: We reviewed clinical charts, including lab results, for more than 80 diabetic and pre-diabetic patients treated at one U.S. outpatient clinic in St. Louis, Missouri between February 2017 and December 2019. Data included patient demographics, treatment data, lab and neuropathy tests, and self-reported patient health status questions. The explanatory variable was number of months of MII treatment. Treatments are 3–4 h in length, with two intensive infusions the first week and one treatment each week thereafter, usually for 12 weeks total. Lab tests were at 12-week intervals. Generalized linear modeling and t-tests assessed the significance of differences between patients' baseline lab values, neuropathy measures, and health status before treatment vs. after final treatment. Results: Number of MII treatments per patient ranged from 1 to 262, over 1–24 months. Time in MII treatment was significantly associated with reductions in HbA1c by nearly 0.04 points per month, and triglycerides declined 3 points per month. Neuropathy measures of large toe vibratory sensation (clanging tuning fork) improved significantly, as did patient-reported health and feelings of improvement since beginning treatment. Discussion: The MII therapy appears to be efficacious in treating diabetic patients, particularly those with complications like neuropathy. Our findings affirmed several other studies. We uniquely incorporated patient health questionnaires, and empirically studied MII treatment efficacy for diabetes in a population large enough to permit statistically valid inferences. With multiple waves of data for over 80 patients, this is one of the most extensive quantitative studies of microburst insulin infusion therapy conducted to date, with protocols more uniformly implemented and survey instruments more consistently administered by the same clinical team. Given the advances in insulin infusion therapy brought by MII, and early indications of its efficacy, the time is right for more in-depth studies of the outcomes patients can achieve, the physiological mechanisms by which they occur, MII's comparative effectiveness vis-à-vis traditional treatments, and cost-effectiveness.